History of the United Netherlands, 1594 - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"History of the United Netherlands, 1594" by John Lothrop Motley is a historical account written during the late 19th century. The book examines the complex political and military events in the Netherlands leading up to the Twelve Years' Truce with Spain, focusing on the pivotal role played by Prince Maurice and the military strategies employed during sieges such as Gertruydenberg and Groningen. The opening of the narrative sets the stage for a detailed account of the military campaigns under Prince Maurice as he innovates battlefield strategies and lays siege to significant cities held by Spanish forces. The text introduces the tactical approaches that Maurice employs to ensure the success of his operations while detailing the shifting allegiances within the local populace and the chaotic situation faced by both besiegers and besieged. Key events, such as the capitulation of Gertruydenberg and conflicts between commanders, showcase the transformative nature of warfare in that era, and the implications of these sieges on the broader struggle for Dutch independence are intimated. (This is an automatically generated summary.)
Release date is 2004-01-01
This eBook was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648